2006
DOI: 10.1063/1.2213929
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature ferromagnetism in (Mn, N)-codoped ZnO thin films prepared by reactive magnetron cosputtering

Abstract: (Mn, N)-codoped ZnO films were grown on fused silica substrates by reactive magnetron cosputtering. X-ray diffraction measurements reveal that the films have the single-phase wurtzite structure with c-axis preferred orientation. X-ray photoelectron spectroscopy studies indicate the incorporation of both divalent Mn2+ and trivalent N3− ions into ZnO lattice. Acceptor doping with nitrogen partly compensates the “native donors,” which results in a low electron concentration of 3.16×1016cm−3 though p-type conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 32 publications
7
48
0
Order By: Relevance
“…Yan et al 2007 reported the first-principle calculations and suggest that the N substitution for the O site in Mn-doped ZnO can change the interaction of neighboring Mn-Mn pairs from antiferromagnetic to ferromagnetic, and accordingly, they observed that the effective magnetic moment per Mn is greatly enhanced for N co-doped Mn:ZnO thin films grown using inductively coupled plasma enhanced chemical vapor deposition method. Xu et al 2006 suggested the bound magnetic polaron model for long-range ferromagnetic coupling between Mn 2? -Mn 2?…”
Section: ¼ Kk=b Cos Hmentioning
confidence: 99%
See 2 more Smart Citations
“…Yan et al 2007 reported the first-principle calculations and suggest that the N substitution for the O site in Mn-doped ZnO can change the interaction of neighboring Mn-Mn pairs from antiferromagnetic to ferromagnetic, and accordingly, they observed that the effective magnetic moment per Mn is greatly enhanced for N co-doped Mn:ZnO thin films grown using inductively coupled plasma enhanced chemical vapor deposition method. Xu et al 2006 suggested the bound magnetic polaron model for long-range ferromagnetic coupling between Mn 2? -Mn 2?…”
Section: ¼ Kk=b Cos Hmentioning
confidence: 99%
“…Assadi et al 2009 also predicted enhanced ferromagnetism in ZnO co-doped with Co and N. Yan et al 2007 reported that N incorporation in Mn:ZnO thin films synthesized using chemical vapor deposition method, greatly enhanced the magnetic moment per Mn. Xu et al 2006 reported ferromagnetism in N and Mn co-doped ZnO thin films grown using reactive magnetron sputtering and suggested bound magnetic polaron model for the observed magnetism. Different groups have observed high-T C ferromagnetism in ZnO:Mn films by doping group V elements (N, P, and As) as p-type dopants and suggested the activation of ferromagnetism to the holes induction by the doping of acceptors (Kittistved et al 2005;Xu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, (Mn,N)-codoped ZnO nanopillars prepared by RF magnetron sputtering showed enhanced RTFM as compared to ZnO:Mn prepared using the same approach [65]. Based on the appearance of acceptors as evidenced from Hall measurement, the ferromagnetism in (Mn,N)-codoped ZnO nanopillars was ascribed to magnetic interaction between the bound magnetic polarons (BMPs) [66][67][68] formed between the compensated holes generated by N doping and localized magnetic cations created by Mn doping. Besides H or N, codoping with other elements has also been attempted.…”
Section: Experimental Results On Zno:mn and Zno:co Nanostructuresmentioning
confidence: 99%
“…However, the doping of ZnO with Cu 2+ ions cannot modify ZnO structure [20]. In turn, the Y 3+ element belong to rare earth periodic family [5] [6], the importance of Y 3+ is its capacity for tailoring the optical properties of ZnO, because Y 3+ doping decrease the energy band gap of ZnO [7]. The Y 3+ surface hinders crystalline growth and promotes vacancies generation [21].…”
Section: Introductionmentioning
confidence: 99%